2005
DOI: 10.1002/cbm.26
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis dependence and mental health perception amongst people diverted by police after arrest for cannabis-related offending behaviour in Australia

Abstract: Young cannabis users in Queensland who come into contact with the police are more likely than not to be dependent on the drug. Their high levels of psychopathology suggest that they are better placed in healthcare rather than the criminal justice system, and that appropriately responsive mental healthcare programmes are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…This study found that 55% of all the clients met the criteria for cannabis dependence, a number close to the 60% findings of an Australian study of individuals diverted by police after arrest for cannabis-related offences [19]. Legally coerced clients were less impaired at admission, were more likely to stay in treatment longer and to complete treatment, and were less likely to leave against program advice but were more likely to be asked to leave as a result of rule violations.…”
Section: Discussionsupporting
confidence: 75%
“…This study found that 55% of all the clients met the criteria for cannabis dependence, a number close to the 60% findings of an Australian study of individuals diverted by police after arrest for cannabis-related offences [19]. Legally coerced clients were less impaired at admission, were more likely to stay in treatment longer and to complete treatment, and were less likely to leave against program advice but were more likely to be asked to leave as a result of rule violations.…”
Section: Discussionsupporting
confidence: 75%
“…The authors found that the severity of symptoms within the 'anxiety-dependency' cluster in cannabis users increased as their level of cannabis use increased (Clough et al, 2005). This seems to be particularly evident among women, as observed in cannabis-dependent individuals arrested for marijuana-related offending behaviour (Feeney et al, 2005). State anxiety level was also one of the main predictors of increased severity of cannabis use (Spalletta et al, 2007), while the marijuana use increased the risk for anxiety symptoms and catastrophic thinking (Zvolensky et al, 2006b).…”
Section: Evidence Of the Association Between Anxiety And Cannabis Usementioning
confidence: 90%
“…Applying the GHQ-28 threshold for psychiatric case identification (caseness), cannabis dependent participants had significantly higher level of caseness across all subscales of somatic concerns, anxiety, social dysfunction and depression. Dependent women registered the highest proportion of psychopathology, particularly anxiety and social dysfunction [17].…”
Section: Substance Use Somatic Symptoms and Anxiety Disordersmentioning
confidence: 99%